Customised next-generation sequencing multigene panel to screen a large cohort of individuals with chromatin-related disorder. Issue 11 (13th March 2020) - Squeo, Gabriella Maria; Augello, Bartolomeo; Massa, Valentina; Milani, Donatella; Colombo, Elisa Adele; Mazza, Tommaso; Castellana, Stefano; Piccione, Maria; Maitz, Silvia; Petracca, Antonio; Prontera, Paolo; Accadia, Maria; et al.
Abstract : Background: The regulation of the chromatin state by epigenetic mechanisms plays a central role in gene expression, cell function, and maintenance of cell identity. Hereditary disorders of chromatin regulation are a group of conditions caused by abnormalities of the various components of the epigenetic machinery, namely writers, erasers, readers, and chromatin remodelers. Although neurological dysfunction is almost ubiquitous in these disorders, the constellation of additional features characterizing many of these genes and the emerging clinical overlap among them indicate the existence of a community of syndromes. The introduction of high-throughput next generation sequencing (NGS) methods for testing multiple genes simultaneously is a logical step for the implementation of diagnostics of these disorders. Methods: We screened a heterogeneous cohort of 263 index patients by an NGS-targeted panel, containing 68 genes associated with more than 40 OMIM entries affecting chromatin function. Results: This strategy allowed us to identify clinically relevant variants in 87 patients (32%), including 30 for which an alternative clinical diagnosis was proposed after sequencing analysis and clinical re-evaluation. Conclusion: Our findings indicate that this approach is effective not only in disorders with locus heterogeneity, but also in order to anticipate unexpected misdiagnoses due to clinical overlap among cognate disorders. Finally, this work highlights the utility of a prompt diagnosis in such a clinically and genetically heterogeneous group of disorders that we propose to group under the umbrella term of chromatinopathies.